2006
DOI: 10.1111/j.1540-6237.2006.00416.x
|View full text |Cite
|
Sign up to set email alerts
|

Acculturation Effects on Trust in National and Local Government Among Mexican Americans*

Abstract: The objectives of this article are to examine the impact of acculturation on the levels of trust in both the national and local governments in a long-term minority-majority community and to consider the effect on Mexican Americans' level of trust of long-term co-ethnic control of local government. Copyright (c) 2006 Southwestern Social Science Association.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
27
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(37 citation statements)
references
References 29 publications
4
27
1
Order By: Relevance
“…Similar results are reported in studies concerning Latin American immigrants; in this particular category, those who had migrated to the USA tend to report higher political trust than members of the white majority population (Michelson 2003;Weaver 2003;Wenzel 2006).…”
Section: Empirical Findings In Previous Researchsupporting
confidence: 74%
“…Similar results are reported in studies concerning Latin American immigrants; in this particular category, those who had migrated to the USA tend to report higher political trust than members of the white majority population (Michelson 2003;Weaver 2003;Wenzel 2006).…”
Section: Empirical Findings In Previous Researchsupporting
confidence: 74%
“…Anglos, for instance, have higher levels of trust than African Americans (Wenzel, 2006). The evidence for Latinos, however, is more mixed (Wenzel, 2006).…”
Section: Latino Determinants Of Trustmentioning
confidence: 99%
“…Anglos, for instance, have higher levels of trust than African Americans (Wenzel, 2006). The evidence for Latinos, however, is more mixed (Wenzel, 2006). Early studies of trust among Latinos identified a lower level of trust among Latinos when compared with Whites (de La Garza et al, 1992).…”
Section: Latino Determinants Of Trustmentioning
confidence: 99%
See 2 more Smart Citations